A new species of Chiridota (Echinodermata: Holothuroidea: Apodida: Chiridotidae) from Japan, and First record of C. rigida from Japan - Yamana, Yusuke; Tanaka, Hayato (Zootaxa, 2017)
A new apodid sea cucumber, Chiridota impatiens sp. nov., is described from the intertidal zone of Okinawa, Japan, and C. rigida Semper, 1867 is also described from the intertidal zone of Wakayama, as new to Japan. C. impatiens sp. nov. is approximately 60–70 mm, with 12 tentacles and 4–7 pairs of digits per tentacle, red or reddish brown in living specimens. The tentacles contain curved rod ossicles, with spinous processes and many branches in C. rigida, however, in C. impatiens sp. nov., the curved rod ossicles are crescent-shaped, sometimes distally, with spinous processes and rarely a few branches on the circumference. In both species, the body wall contains flattened rod ossicles, mostly present along the longitudinal muscle and mesentery, curved rod ossicles primarily in the body wall, and wheel ossicles only in the wheel-papillae. In C. rigida, the contents of the wheel-papillae form a hemispherical sack-shaped structures, in which the teeth-side of the wheel ossicles mostly faces towards the outside of the body. In C. impatiens sp. nov., the contents of the wheel-papillae form a cord-shaped structure (present in both preserved and living specimens), in which the teeth-side of the wheel ossicles faces various directions, and that can be induced to break through the skin of the papillae if stimulated in living specimens.